2020
DOI: 10.1039/d0sc90150d
|View full text |Cite
|
Sign up to set email alerts
|

A diverse view of science to catalyse change

Abstract: Valuing diversity leads to scientific excellence, the progress of science and, most importantly, it is simply the right thing to do. We must value diversity not only in words, but also in actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…40 Connecting the chemical worlds also involves embracing diversity in chemistry, meaning including the experiences and knowledge of people from different backgrounds, origins, and career paths. 41…”
Section: Planetary Boundariesmentioning
confidence: 99%
“…40 Connecting the chemical worlds also involves embracing diversity in chemistry, meaning including the experiences and knowledge of people from different backgrounds, origins, and career paths. 41…”
Section: Planetary Boundariesmentioning
confidence: 99%
“…We believe in the importance of representing the nanocrystal community diversity fully in terms of background, career stage, etc . The News in Nanocrystals seminar started and continues to run at a time when conversations about diversity, inclusion, equality, and representation came to the forefront of the chemistry community in the United States , and other countries. , As organizers of a virtual public event, it is our responsibility to be conscious of gender and racial imbalances and the challenges that historically-excluded minorities face in science (for example, we canceled the second planned seminar on June 10 of 2020 during the global #ShutDownSTEM day to express solidarity and support of the efforts against racism in science and society). We aim to run all aspects of the seminar by adhering to the principles of diversity, equality, and inclusion.…”
Section: Statement Of Mission and Valuesmentioning
confidence: 99%
“…More recently in the UK, analysis of the longitudinal British Cohort Study revealed that people from white ethnic backgrounds were around 1.5 times more likely to have worked in the sciences than those from minority ethnic groups . Despite continued, long-standing awareness of underrepresentation of minoritized individuals in the sciences and “calls-to-action” over many decades, it remains an issue that needs to be urgently addressed today. …”
Section: Introductionmentioning
confidence: 99%